Manganese-based layered oxide positive electrode material and preparation method and application thereof

By doping rare earth element Y into the positive electrode material of sodium ion battery and controlling its crystal structure and electronic structure, the problems of structural degradation and poor electrochemical performance of sodium ion battery are solved under high pressure, and the structural stability and electrochemical performance of the material are significantly improved.

CN120191967AInactive Publication Date: 2025-06-24CHINA WEST NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510393315.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-06-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The sodium ion battery positive electrode material has problems such as structural degradation, slow diffusion kinetics of sodium ion, Mn3+ Jahn Teller effect leads to lattice distortion, Mn3+ distortion reaction causes the dissolution of transition metal ions, severe interfacial side reactions and interface reconstruction, which limits its electrochemical performance.

Method used

Through the doping of rare earth metal element Y, the crystal structure and electronic structure of manganese-based layered oxide are regulated, and the octahedral site of the transition metal layer is preferred, the layer spacing is expanded, the Na+ migration energy barrier is reduced, and the Jahn Teller effect and P2-O2 phase transition of Mn3+ are suppressed.

Benefits of technology

It significantly improves the structural stability and electrochemical performance of manganese-based layered oxides, alleviates the capacity attenuation problem during charging and discharging, and improves the cyclic stability and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120191967A_ABST
    Figure CN120191967A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese-based layered oxide positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of sodium-ion battery materials. The chemical formula of the positive electrode material is Na < 0.67 > Mn < 1-x > Y < x > O < 2 By doping the rare earth metal element Y, the crystal structure and the electronic structure of the manganese-based layered oxide are effectively regulated and controlled, and the structural stability of the material can be enhanced while the Na < + > migration energy barrier is reduced. A sol-gel method is combined with a gradient annealing process to regulate and control the preferred growth orientation of the crystal face of the material, and the crystal structure and morphology of the material can be accurately regulated and controlled by controlling the pH value, the reaction temperature and the calcination condition, so that the cycling stability and the rate capability of the material are remarkably improved, and the preparation method is simple and convenient. And a new research thought is provided for developing a sodium battery positive electrode material with high stability and high power density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium-ion battery materials, and particularly relates to a manganese-based layered oxide cathode material, a preparation method thereof, and an application thereof. Background Art

[0003] The cathode material of a sodium-ion battery is one of the key factors determining its electrochemical performance. At present, the technical routes of cathode materials mainly include layered transition metal oxides, Prussian blue analogs, and polyanion compounds. Among them, manganese-based layered oxides (such as Na x MnO2) have become a research hotspot for sodium-ion battery cathode materials due to their high specific capacity, rich resources, simple synthesis method, environmental friendliness, and low cost. P2-type manganese-based layered oxides have become one of the most promising candidates for sodium-ion battery cathode materials due to their high theoretical capacity and rich raw materials. However, this material has the following scientific problems: phase transition under high voltage (>4.0V) leads to structural degradation (P2-O2 phase transition); the ordered arrangement of Na + / vacancies results in slow sodium-ion diffusion kinetics; the Jahn Teller effect of Mn 3+ causes lattice distortion; the disproportionation reaction of Mn 3+ results in the dissolution of transition metal ions, leading to capacity loss; serious interfacial side reactions and interfacial reconstruction; there is a defect phase behavior during the first charging process, resulting in limited application of the full battery.

[0004] To solve the above key problems, current related research work shows that the electrochemical performance of the sodium-ion battery cathode can be modified to varying degrees through ion doping, surface modification, morphology control, and comprehensive modification strategies. Among them, ion doping, as an effective modification strategy, can not only effectively inhibit the Jahn Teller effect of Mn 3+ but also alleviate the phase transition of the cathode material under high voltage. Rare earth elements are often used for material modification due to their unique electronic structures and chemical properties. Among them, yttrium (Y), as a rare earth element, has excellent stability and the ability to regulate electrochemical performance, but its application research in manganese-based layered oxides is less. Summary of the Invention

[0005] In view of the above-mentioned prior art, the present invention provides a manganese-based layered oxide cathode material, a preparation method thereof, and an application thereof to solve the technical problem of poor electrical performance of the sodium-ion battery cathode material in the prior art.

[0006] To achieve the above object, the technical solution adopted by the present invention is to provide a manganese-based layered oxide cathode material, and the molecular formula of the manganese-based layered oxide cathode material is Na 0.67 Mn 1-x Yx O2, where 0.005 ≤ x ≤ 0.2; the crystal form of the manganese-based layered oxide cathode material is hexagonal system and belongs to the P63 / mmc space group.

[0007] Based on the above technical solutions, the present invention can also be improved as follows.

[0008] Further, the molecular formula of the manganese-based layered oxide cathode material is Na 0.67 Mn 0.99 Y 0.01 O2.

[0009] The present invention also discloses a preparation method of the above manganese-based layered oxide cathode material, including the following steps: S1: Mix a sodium source and a citric acid solution to obtain solution A; S2: Dissolve a manganese source and a yttrium source in water according to a molar ratio to obtain solution B; S3: Heat solution B, and then add solution A to solution B under stirring; then raise the temperature to 50 - 100 °C and keep the reaction for 8 - 10 h to obtain a gel, and maintain the pH of the system at 5 - 8 during the reaction; S4: Dry the gel obtained in S3 into a dry gel, then grind it into powder, and then calcine it in an air atmosphere, and then cool it to room temperature to obtain the product.

[0010] Further, the sodium source is at least one of sodium acetate, sodium hydroxide, sodium carbonate, sodium nitrate and sodium chloride; the concentration of the citric acid solution is 1 M.

[0011] Further, the concentration of the sodium source in solution A is 0.5 mol / L.

[0012] Further, the manganese source is at least one of manganese acetate, manganese nitrate, manganese sulfate and manganese chloride; the yttrium source is at least one of yttrium nitrate, yttrium acetate, yttrium chloride, yttrium carbonate and yttrium sulfate.

[0013] Further, the final heating temperature of solution B in S3 is 50 - 100 °C.

[0014] Further, the drying temperature in S4 is 80 - 120 °C and the drying time is 12 - 24 h.

[0015] Further, the calcination method in S4 is: first raise the temperature to 400 - 600 °C and keep it for pre-calcination for 2 - 10 h; then raise the temperature to 700 - 1000 °C and keep it for sintering for 5 - 20 h.

[0016] The present invention also discloses the application of the above manganese-based layered oxide cathode material in the preparation of sodium ion batteries.

[0017] The beneficial effects of the present invention are: 1. The present invention provides a manganese-based layered oxide cathode material. The core of the present invention lies in effectively regulating the crystal structure and electronic structure of the manganese-based layered oxide through the doping of rare earth metal element Y. Specifically, Y 3+ (ionic radius 0.90 Å) preferentially occupies the octahedral sites in the transition metal layer. Its relatively large ionic radius generates a lattice expansion effect, expanding the layer spacing of the original material and reducing the Na + migration barrier, which is beneficial to the rapid deintercalation and intercalation of sodium ions; in addition, Y 3+ is an electrochemically inactive ion, which effectively inhibits the Jahn-Teller distortion and P2-O2 phase transition of Mn 3+ during the cycling process as a structural pillar. Moreover, the doping of Y 3+ can reduce the average oxidation state of manganese, thereby reducing the dissolution of manganese elements, significantly alleviating the capacity decay problem while enhancing the structural stability of the material.

[0018] 2. The present invention prepares the manganese-based layered oxide cathode material by using the sol-gel method combined with the gradient annealing process. This method regulates the preferred growth orientation of the crystal planes of the material, increasing the exposure ratio of the highly active {010} crystal plane. This crystal plane cluster has an open two-dimensional Na + diffusion channel, which is beneficial to the rapid deintercalation and intercalation of sodium ions; the strong covalent nature of the Y-O bond reduces the electron localization effect of the Mn 3+ / Mn 4+ redox pair, optimizing the electronic conductivity of the material. The present technology realizes the multi-scale regulation of the material through the doping of rare earth metal element Y, ultimately achieving a significant improvement in the cycle stability and rate performance of the material, providing a new research idea for the development of high-stability and high-power-density sodium battery cathode materials.

[0019] 3. The present invention prepares the manganese-based layered oxide cathode material by using the sol-gel method. The process is simple, the conditions are mild, no complex equipment is required, and it is suitable for industrial production. Common sodium sources, manganese sources, and yttrium sources are selected as raw materials, which are low-cost and easy to obtain. By controlling the pH value, reaction temperature, and calcination conditions, the crystal structure and morphology of the material can be precisely regulated to ensure the consistency and high performance of the product. In addition, no inert gas protection is required during the preparation process, further reducing the production cost. Description of the Drawings

[0020] Figure 1 SEM image of Na 0.67 Mn 0.99 Y 0.01 O2 prepared in Example 1; Figure 2 TEM image of Na 0.67 Mn 0.99 Y 0.01 O2 prepared in Example 1; Figure 3 The X-ray diffraction pattern of Na 0.67 Mn 0.99 Y 0.01 MnO2 prepared in Example 1; Figure 4 The cyclic voltammogram of the sodium-ion battery assembled with the manganese-based layered oxide cathode material in Example 1; Figure 5 The cycling performance graph of the sodium-ion batteries assembled with the cathode materials in Example 1 and Comparative Example 1 at a small current; Figure 6 The cycling performance graph of the sodium-ion batteries assembled with the cathode materials in Example 1 and Comparative Example 1 at a large current; Figure 7 The charge-discharge capacity-voltage graph of the sodium-ion battery assembled with the high-entropy layered oxide in Example 1 as the cathode material. Detailed implementation manners

[0021] The following combines examples to make a detailed description of the specific implementation manners of the present invention. Example

[0022] A manganese-based layered oxide cathode material, the chemical formula of the cathode material is Na 0.67 Mn 0.99 Y 0.01 MnO2; it is prepared through the following steps: S1: Dissolve anhydrous Na2CO3 in 40 mL of a 1 M citric acid solution to obtain solution A with a concentration of Na + of 1 mol / L; S2: Weigh manganese acetate tetrahydrate and yttrium nitrate tetrahydrate according to the molar ratio of Na + :Mn 2+ :Y 3+ =0.67:0.99:0.01 (Na is in excess by 5%), dissolve them in 40 mL of deionized water to obtain solution B; S3: Heat solution B to 50 °C under stirring, and then slowly add solution A; test the pH value of the mixed solution with a pH meter under stirring, and adjust the pH value to 6 with ammonia water, then raise the temperature to 80 °C, maintain the temperature and pH, and react for 10 hours to form a gel; S4: Take out the stir bar, transfer the gel to an oven, and dry it at 120 °C for 24 h to form a dry gel; S5: Grind the dry gel into powder, and then calcine it in an air atmosphere. The calcination method is: first raise the temperature to 450 °C and carry out constant-temperature pre-calcination for 6 h; then raise the temperature to 950 °C and keep it warm for sintering for 15 h; after calcination, naturally cool it to room temperature to obtain the manganese-based layered oxide cathode material. Example

[0023] A manganese-based layered oxide cathode material, the chemical formula of the cathode material is Na 0.67 Mn 0.99 Y 0.01 O2; It is prepared through the following steps: S1: Dissolve anhydrous Na2CO3 in 40 mL of a 1 M citric acid solution to obtain a solution A with a concentration of 1 mol / L of Na + ; S2: Weigh manganese acetate tetrahydrate and yttrium nitrate tetrahydrate according to the molar ratio of Na + :Mn 2+ :Y 3+ =0.67:0.99:0.01 (with 5% excess Na), and co-dissolve them in 40 mL of deionized water to obtain solution B; S3: Heat solution B to 100 °C with stirring, and then slowly add solution A; measure the pH value of the mixed solution with a pH meter under stirring, and adjust the pH value to 5 with ammonia water; maintain the temperature of the reaction system at 100 °C and the pH at 5, and react for 8 hours under these conditions to form a gel; S4: Take out the stir bar, transfer the gel to an oven, and dry it at 80 °C for 24 h to form a dry gel; S5: Grind the dry gel into powder, and then calcine it in an air atmosphere. The calcination method is as follows: first heat it to 400 °C and carry out constant-temperature pre-calcination for 10 h; then heat it to 700 °C and keep it warm for sintering for 20 h; after calcination, naturally cool it to room temperature to obtain the manganese-based layered oxide cathode material. Example

[0024] A manganese-based layered oxide cathode material, the chemical formula of the cathode material is Na 0.67 Mn 0.99 Y 0.01 O2; It is prepared through the following steps: S1: Dissolve anhydrous Na2CO3 in 40 mL of a 1 M citric acid solution to obtain a solution A with a concentration of 1 mol / L of Na + ; S2: Weigh manganese acetate tetrahydrate and yttrium nitrate tetrahydrate according to the molar ratio of Na + :Mn 2+ :Y 3+ =0.67:0.99:0.01 (with 5% excess Na), and co-dissolve them in 40 mL of deionized water to obtain solution B; S3: Heat solution B to 50 °C with stirring, and then slowly add solution A; measure the pH value of the mixed solution with a pH meter under stirring, and adjust the pH value to 8 with ammonia water; maintain the temperature of the reaction system at 80 °C and the pH at 8, and react for 10 hours under these conditions to form a gel; S4: Take out the magnetic stir bar, transfer the gel to an oven, and dry it at 100 °C for 12 h to form a dry gel. S5: Grind the dry gel into powder, and then calcine it in an air atmosphere. The calcination method is as follows: first heat it to 600 °C and pre-calcine it at a constant temperature for 2 h; then heat it to 1000 °C and sinter it at a constant temperature for 5 h; after calcination, cool it naturally to room temperature to obtain the manganese-based layered oxide cathode material.

[0025] Comparative Example 1 An oxide cathode material, which is the common Na 0.67 MnO2 in the prior art.

[0026] The properties of the manganese-based layered oxide cathode materials prepared in Examples 1 to 3 of the present invention are similar. Taking the manganese-based layered oxide cathode material in Example 1 as an example, the properties of the cathode material will be described in detail.

[0027] Experimental Example 1: Morphology analysis of the manganese-based layered oxide cathode material Perform SEM test on Na 0.67 Mn 0.99 Y 0.01 O2 in Example 1, and the results are as Figure 1 shown. As can be seen from the figure, the prepared Na 0.67 Mn 0.99 Y 0.01 O2 shows a hexagonal layered structure with a size of 2 - 3 μm. The layered structure is beneficial to the rapid deintercalation and insertion of sodium ions, providing a good ion transport channel.

[0028] Perform TEM test on Na 0.67 Mn 0.99 Y 0.01 O2 in Example 1, and the results are as Figure 2 shown. As can be seen from the figure, the prepared Na 0.67 Mn 0.99 Y 0.01 O2 has a relatively large interlayer spacing, about 0.5 - 0.6 nm, which further promotes the diffusion kinetics behavior of sodium ions and improves the electrochemical performance of the material.

[0029] Perform XRD analysis on Na 0.67 Mn 0.99 Y 0.01 O2 in Example 1, and the results are as Figure 3 shown. As can be seen from the figure, the XRD diffraction curve shows that the prepared Na 0.67 Mn 0.99 Y 0.01All the diffraction peaks in the O2 cathode are in good agreement with the standard card of the P2-type structure in the hexagonal crystal system with the space group P63 / mmc, and no other impurity peaks appear, indicating that the material has a typical P2-phase layered structure, and the doping of Y 3+ does not destroy the crystal structure of the material, but enhances its stability.

[0030] Experimental Example 2: Performance Analysis of Manganese-Based Layered Oxide Cathode Materials Based on the above-mentioned manganese-based layered oxide cathode material, a sodium-ion secondary battery with a high energy density is assembled; hard carbon is used as the anode material of the sodium-ion battery, and the manganese-based layered oxide cathode material in Example 1 is used as the cathode material of the sodium-ion battery; the sodium-ion battery is prepared through the following steps: (1) In a stainless-steel glove box under an inert atmosphere, Na 0.67 Mn 0.99 Y 0.01 O2 cathode material, conductive agent, and binder are ground and mixed according to a mass ratio of 85:10:5, and coated on an aluminum foil current collector to make a positive electrode plate; among them, the conductive agent is acetylene black (conductive carbon black or Super P can also be used), the binder is polyacrylic acid (polytetrafluoroethylene or polyvinylidene fluoride can also be used), and the grinding time is 5 minutes; (2) In a stainless-steel glove box under an inert atmosphere, the positive electrode plate is dried at 90 °C and then cut to obtain an electrode plate, and the prepared positive electrode plate is assembled with the negative electrode plate to form a button-type sodium-ion secondary battery; among them, the electrolyte is prepared by mixing 1M NaPF6, EC / DME (v:v = 1:1) and 5% fluoroethylene carbonate by mass fraction, and is assembled in an Ar gas atmosphere stainless-steel glove box with the water and oxygen contents both lower than 1 ppm using glass fiber.

[0031] Using the same method, the positive electrode material in Comparative Example 1 is used as the positive electrode material of the sodium-ion battery to assemble the sodium-ion battery.

[0032] The cycle performance of the battery assembled with the manganese-based layered oxide cathode material in Example 1 as the positive electrode is tested, and the results are as Figure 4 shown. As can be seen from the figure, after the material is cycled 100 times at a rate of 0.5C, the capacity retention rate can reach more than 70%, showing excellent cycle stability.

[0033] The cycle performance of the sodium-ion batteries assembled with the manganese-based layered oxide cathode material in Example 1 and the oxide cathode material in Comparative Example 1 is tested at a small current respectively, and the results are as Figure 5 shown. As can be seen from the figure, the manganese-based layered oxide cathode material in Example 1 can still maintain a high specific capacity at a high rate, indicating that the doping of Y 3+ significantly improves the rate performance of the material.

[0034] The cyclic performance tests of sodium-ion batteries assembled with the manganese-based layered oxide cathode material in Example 1 and the oxide cathode material in Comparative Example 1 were respectively carried out under high current, and the results are as Figure 6 shown. As can be seen from the figure, the manganese-based layered oxide cathode material in Example 1 can still maintain a high specific capacity at high rates, indicating that the unique morphology structure of the material optimizes the sodium-ion transport kinetics and the electrochemistry reaction activity, and significantly improves the rate performance of the material.

[0035] The charge-discharge capacity tests of the sodium-ion secondary battery assembled with the manganese-based layered oxide cathode material in Example 1 were carried out in the voltage range of 1.5~4.5V, and the results are as Figure 7 shown. As can be seen from the figure, the difference in the voltages corresponding to the charge-discharge curve platforms is small, indicating less polarization, and the coincidence degree of the charge-discharge curves during the cycling process is good, indicating good cyclic performance of the material.

[0036] In summary, it can be seen that through the doping of rare earth metal element Y, the present invention significantly improves the structural stability and electrochemical performance of the manganese-based layered oxide, effectively alleviates the problem of capacity decay during the charge-discharge process, and provides a new solution for the development of high-performance sodium-ion batteries.

[0037] Although the specific implementation manners of the present invention have been described in detail in combination with the embodiments, it should not be construed as a limitation on the protection scope of this patent. Within the scope described in the claims, various modifications and deformations that can be made by those skilled in the art without creative labor still fall within the protection scope of this patent.

Claims

1. A manganese-based layered oxide positive electrode material, characterized in that: The molecular formula of the manganese-based layered oxide positive electrode material is Na 0.67 Mn 1-x Y x O2, wherein 0.005≤x≤0.2; the crystal form of the manganese-based layered oxide positive electrode material is hexagonal and belongs to the P63 / mmc space group.

2. The manganese-based layered oxide positive electrode material according to claim 1, characterized in that: The molecular formula of the manganese-based layered oxide positive electrode material is Na 0.67 Mn 0.99 Y 0.01 O2.

3. The method for preparing the manganese-based layered oxide positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: S1: Mix the sodium source and the citric acid solution to obtain solution A; S2: dissolving the manganese source and the yttrium source in water in a molar ratio to obtain solution B; S3: heating solution B, and then adding solution A to solution B under stirring; Then raise the temperature to 50-100°C and keep the temperature to react for 8-10 hours to obtain a gel. During the reaction, the pH of the system is maintained at 5-8. S4: Dry the gel obtained in S3 into a dry gel, grind it into powder, calcine it in an air atmosphere, and then cool it to room temperature to obtain the dry gel.

4. The preparation method according to claim 3, characterized in that: The sodium source is at least one of sodium acetate, sodium hydroxide, sodium carbonate, sodium nitrate and sodium chloride; and the concentration of the citric acid solution is 1M.

5. The preparation method according to claim 4, characterized in that: The sodium Na in solution A + The concentration is 1 mol / L.

6. The preparation method according to claim 3, characterized in that: The manganese source is at least one of manganese acetate, manganese nitrate, manganese sulfate and manganese chloride; the yttrium source is at least one of yttrium nitrate, yttrium acetate, yttrium chloride, yttrium carbonate and yttrium sulfate.

7. The preparation method according to claim 3, characterized in that: The final heating temperature of solution B in S3 is 50~100℃.

8. The preparation method according to claim 3, characterized in that: In S4, the drying temperature is 80~120℃ and the drying time is 12~24h.

9. The preparation method according to claim 8, characterized in that: The calcination method in S4 is: first increase the temperature to 400~600℃, and pre-calcine at a constant temperature for 2~10h; then increase the temperature to 700~1000℃, and sinter at a constant temperature for 5~20h.

10. Use of the manganese-based layered oxide positive electrode material according to any one of claims 1 to 2 in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • P2-phase sodium ion battery cathode material doped with rare earth metal elements and preparation method thereof

    CN111129483A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN113889619A

  • Layered oxide material and preparation method thereof

    CN117023642A

  • Layered high-entropy oxide positive electrode material of sodium ion battery, preparation method of layered high-entropy oxide positive electrode material, positive electrode plate and sodium ion battery

    CN119170795A